2021
DOI: 10.2106/jbjs.20.02033
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Unplanned Surgery Due to Delayed Diagnosis of Occult Ipsilateral Femoral Neck Fractures Associated with Femoral Shaft Fractures

Abstract: Background:The purpose of the present study was to investigate the effectiveness of using the computed tomography (CT) capsular sign with lipohemarthrosis of the hip joint as a selective indicator for preoperative magnetic resonance imaging (MRI) of the hip or prophylactic fixation of the ipsilateral femoral neck for the prevention of unplanned surgery due to delayed diagnosis of occult ipsilateral femoral neck fractures in patients with high-energy femoral shaft fractures.Methods: We evaluated the CT capsular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“… 2 , 3 , 5 - 7 , 13 This challenge has been noted in multiple studies and is largely due to nondisplaced or minimally displaced femoral neck fractures. 7 , 13 - 15 Owing to this rate of missed injuries, Tornetta et al 3 developed a protocol including 2-mm cut CT scan and internal rotation hip radiographs. This protocol effectively reduced the rates of delayed diagnosis by 91% compared with the previous year.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 5 - 7 , 13 This challenge has been noted in multiple studies and is largely due to nondisplaced or minimally displaced femoral neck fractures. 7 , 13 - 15 Owing to this rate of missed injuries, Tornetta et al 3 developed a protocol including 2-mm cut CT scan and internal rotation hip radiographs. This protocol effectively reduced the rates of delayed diagnosis by 91% compared with the previous year.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Computed tomography (CT) is a diagnosis tool for femoral neck fractures and provides preoperative evaluation for helping to choose the best treatment and provide better surgical and clinical outcomes. 16 , 17 Quantitative analysis of bone-texture features from CT scans has been actively applied to evaluate the status, quality, or microarchitecture of bones. 18 Park et al demonstrated the value of CT in prediction of avascular necrosis after femoral neck fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Totally 4.5 million elderly people worldwide become disabled due to hip fractures every year, including about 1.7 million patients with FNF [ 1 , 2 ]. Such fractures are rarely treated conservatively, but usually treated by cannulated screw internal fixation, femoral head arthroplasty or total hip arthroplasty [ 3 , 4 ]. The type of fractures is one of the important factors determining the treatment programs.…”
Section: Introductionmentioning
confidence: 99%